2007
DOI: 10.1074/jbc.m702291200
|View full text |Cite
|
Sign up to set email alerts
|

Interorganelle Trafficking of Ceramide Is Regulated by Phosphorylation-dependent Cooperativity between the PH and START Domains of CERT

Abstract: The synthesis and transport of lipids are essential events for membrane biogenesis. However, little is known about how intracellular trafficking of lipids is regulated. Ceramide is synthesized at the endoplasmic reticulum (ER) and transported by the ceramide transfer protein CERT to the Golgi apparatus, where it is converted to sphingomyelin. CERT has a phosphoinositidebinding pleckstrin homology (PH) domain for Golgi-targeting and a lipid transfer START domain for intermembrane transfer of ceramide. We here s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
219
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 111 publications
(243 citation statements)
references
References 31 publications
22
219
2
Order By: Relevance
“…In the case of CERT, the Hanada group has shown that phosphorylation inhibits CERT-dependent ceramide transport and that this phosphorylation is regulated by sphingolipid levels (Kumagai et al 2007). Specifically, pharmacologic inhibition of SPT or enzymatic degradation of plasma membrane sphingomyelin induces CERT dephosphorylation and activation, which may enable a compensatory increase in sphingolipid production (Kumagai et al 2007).…”
Section: Regulation Of Sphingolipid Transport and Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of CERT, the Hanada group has shown that phosphorylation inhibits CERT-dependent ceramide transport and that this phosphorylation is regulated by sphingolipid levels (Kumagai et al 2007). Specifically, pharmacologic inhibition of SPT or enzymatic degradation of plasma membrane sphingomyelin induces CERT dephosphorylation and activation, which may enable a compensatory increase in sphingolipid production (Kumagai et al 2007).…”
Section: Regulation Of Sphingolipid Transport and Turnovermentioning
confidence: 99%
“…In the case of CERT, the Hanada group has shown that phosphorylation inhibits CERT-dependent ceramide transport and that this phosphorylation is regulated by sphingolipid levels (Kumagai et al 2007). Specifically, pharmacologic inhibition of SPT or enzymatic degradation of plasma membrane sphingomyelin induces CERT dephosphorylation and activation, which may enable a compensatory increase in sphingolipid production (Kumagai et al 2007). An additional mechanism regulating sphingolipid transport is suggested from the fact that both CERT and FAPP2 contain pleckstrin homology (PH) domains that bind to phosphatidylinositol-4-phosphate (PI4P), a lipid that serves as a key Golgi marker (Di Paolo and De Camilli 2006).…”
Section: Regulation Of Sphingolipid Transport and Turnovermentioning
confidence: 99%
“…This interaction is required for CERT to extract ceramide from the ER before transportation of ceramide to the Golgi apparatus. We also showed that the SR motif in CERT is phosphorylated at multiple Ser/Thr residues and that hyperphosphorylation of these sites results in down-regulation of ceramide trafficking function of CERT (21). We, therefore, were interested in determining whether PP2C⑀ associated with VAPA regulates CERT function through dephosphorylation.…”
Section: Pp2c⑀ Ismentioning
confidence: 99%
“…CERT consists of several distinct domains including a Steroidogenic acute regulator-related lipid transfer (START) domain capable of specifically extracting ceramide from membrane, a pleckstrin homology (PH) domain that serves to target the Golgi apparatus by recognizing phosphatidylinositol 4-monphophatate, and a FFAT motif, which interacts with VAPA. In addition to these functional domains, CERT possesses a regulatory sequence referred to as a serine repeat (SR) motif between the PH domain and FFAT motif (21). The Ser/ Thr residues of the SR motif are phosphorylated in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation